การศึกษาสภาพการบริหารโรงเรียนตามแนวคิดการมองโลกทางวิชาการเชิงบวก ในการยกระดับผลสัมฤทธิ์ทางการเรียนของนักเรียน - เพ็ชรอินทร์, ฐิติรัตน์; เจริญกุล, นันทรัตน์; กุโลภาส, ธีรภัทร (Journal of Education Studies, Chulalongkorn University, 2019)
The research objectives were to study the current and desirable states of school management according to the concept of academic optimism for enhancing students’ achievements. The research applied a mixed method research design. The sample comprised 395 primary schools under the Office of the Basic Education Commission, by using Stratified Random Sampling. The 1,580 respondents were school administrators, the Head of Academic Management Group and teachers. The instruments used in this research were questionnaires and evaluation forms. The data were analyzed by mean and standard deviation. The results showed that the current state of school management according to the concept of academic optimism for enhancing students’ achievement was at the high level. The aspects with the highest level and the highest average scores were Academic Emphasis and Trust in Parents and Students respectively. The current state with the lowest level was Collective Efficacy. The desirable state of school management to the concept of academic optimism for enhancing students’ achievement was at the high level. The aspects at the highest level were Collective Efficacy and Trust in Parents and Students, respectively. The desirable state with the lowest level was Academic Emphasis.